A systematic review of how daily activities and exercises are recommended following volar plating of distal radius fractures and the efficacy and safety of early versus late mobilisation. (December 2020) - Collis, Julie; Signal, Nada; Mayland, Elizabeth; Clair, Valerie Wright-St
Introduction: Following surgical repair of distal radius fractures, mobilisation timeframes and interventions vary. Early mobilisation (<2 weeks postoperatively) usually includes range of motion exercises and may include recommendations to perform daily activities. The review investigated (i) how early mobilisation was recommended, particularly with respect to wrist use during daily activities and (ii) the efficacy and safety of early versus delayed mobilisation (< or ≥2 weeks). Methods: The study protocol was registered on PROSPERO (CRD42019136490). Five databases were searched for studies that compared early and delayed mobilisation in adults with volar plating of distal radius fractures. The Downs and Black Quality Index and the Template for Intervention Description and Replication checklist were used for quality evaluation. Effect sizes were calculated for range of movement, function and pain at 6–8, 10–12 and 26 weeks. A descriptive analysis of outcomes and mobilisation regimes was conducted. Results: Eight studies with a mean Quality Index score of 20 out of 28 (SD=5.6) were included. Performing daily activities was commonly recommended as part of early mobilisation. Commencing mobilisation prior to two weeks resulted in greater range of movement, function and less pain at up to eight weeks postoperatively than delaying mobilisation until two weeks or later. Discussion: Performance of daily activities was used alongside exercise to promote recovery but without clearly specifying the type, duration or intensity of activities. In combination with exercise, early daily activity was safe and beneficial. Performing daily activities may have discrete advantages. Hand therapists are challenged to incorporate activity-approaches into early mobilisation regimes.